Do Dolphins Rehearse Show-Stimuli When at Rest? Delayed Matching of Auditory Memory - Kremers, Dorothee; Briseño Jaramillo, Margarita; Böye, Martin; Lemasson, Alban; HAUSBERGER, Martine (Frontiers in Psychology, 2011)
The mechanisms underlying vocal mimicry in animals remain an open question. Delphinidae are able to copy sounds from their environment that are not produced by conspecifics. Usually, these mimicries occur associated with the context in which they were learned. No reports address the question of separation between auditory memory formation and spontaneous vocal copying although the sensory and motor phases of vocal learning are separated in a variety of songbirds. Here we show that captive bottlenose dolphins produce, during their nighttime resting periods, non-dolphin sounds that they heard during performance shows. Generally, in the middle of the night, these animals produced vocal copies of whale sounds that had been broadcast during daily public shows. As their life history was fully known, we know that these captive dolphins had never had the opportunity to hear whale sounds before then. Moreover, recordings made before the whale sounds started being broadcast revealed that they had never emitted such sounds before. This is to our knowledge the first evidence for a separation between formation of auditory memories and the process of learning to produce calls that match these memories in a marine mammal. One hypothesis is that dolphins may rehearse some special events heard during the daytime and that they then express vocally what could be conceived as a more global memory. These results open the way for broader views on how animals might rehearse life events while resting or maybe dreaming.